2005
DOI: 10.1113/jphysiol.2005.096131
|View full text |Cite
|
Sign up to set email alerts
|

Vesicles in snake motor terminals comprise one functional pool and utilize a single recycling strategy at all stimulus frequencies

Abstract: At a variety of fast chemical synapses, spent synaptic vesicles are recycled via a large 'reserve' vesicle pool at high stimulus frequencies, and via fast 'local cycling' near release sites (e.g. 'kiss and run' transmitter release) at low stimulus frequencies. We have investigated recycling at the snake neuromuscular junction (NMJ), specifically seeking evidence for local cycling. Activity-dependent staining and destaining of the endocytic probe FM1-43 were directly compared to transmitter release over a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
3
7
2
Order By: Relevance
“…Moreover, the rapid onset of spot appearance is consistent with the time course of bulk endocytosis in central nerve terminals (Clayton et al , 2008). Finally, the slow dissipation of FM 4-64 spots, well after complete internalization of synaptic vesicle membrane (provided by the spH signal) is also consistent with the slow regeneration and scattering of synaptic vesicles from structures created by bulk endocytosis (Richards et al , 2000; 2003; Lin et al , 2005), although not necessarily measurements of endosome dissipation (Teng et al , 2007). If the FM 4-64 spots were not large endosomes, but rather clusters of synaptic vesicles, then the low mobility of these vesicles would likely make them less fusion competent (Gaffield and Betz, 2007).…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, the rapid onset of spot appearance is consistent with the time course of bulk endocytosis in central nerve terminals (Clayton et al , 2008). Finally, the slow dissipation of FM 4-64 spots, well after complete internalization of synaptic vesicle membrane (provided by the spH signal) is also consistent with the slow regeneration and scattering of synaptic vesicles from structures created by bulk endocytosis (Richards et al , 2000; 2003; Lin et al , 2005), although not necessarily measurements of endosome dissipation (Teng et al , 2007). If the FM 4-64 spots were not large endosomes, but rather clusters of synaptic vesicles, then the low mobility of these vesicles would likely make them less fusion competent (Gaffield and Betz, 2007).…”
Section: Discussionsupporting
confidence: 64%
“…However, in contrast to our observations in acute hippocampal slices, RRP vesicles in most other preparations readily mix with a reserve pool over time (Pyle et al, 2000;de Lange et al, 2003). Interestingly, recent studies in the cone photoreceptor terminals (Rea et al, 2004) or in snake motor nerve terminals (Lin et al, 2005) revealed a more streamlined vesicle recycling consistent with a single functional pool of vesicles. Moreover, RRP vesicles in the frog neuromuscular junction also follow a rather isolated recycling pathway and only mix with a reserve pool after very strong and sustained stimulation (Richards et al, 2003;Rizzoli and Betz, 2005).…”
Section: Discussioncontrasting
confidence: 55%
“…Considering that each amphibian motor nerve terminal contains approximately 700 active zones (Soyoun Cho and S.D.M., unpublished observations), the frequency of spontaneous fluctuations in Ca 2+ entry would be about 10/nerve terminal/second. In this light, it is likely that the increase in Ca 2+ fluctuations leads to the reported general elevation of MEPP frequency, and that the strong Ca 2+ entry events might instead trigger the large synchronous bursts in MEPP frequency observed in addition to the general increase in asynchronous MEPP frequency (Betz et al, 1992;de Paiva et al, 1999;Henkel et al, 1996;Lin et al, 2005;Ribchester et al, 1994;Smith and Betz, 1996).…”
Section: Glycerotoxin Promotes a Long-term Increase In Basal Intratermentioning
confidence: 99%
“…Styryl dyes such as FM1-43 have been widely used to investigate synaptic-vesicle recycling at the NMJ (Betz et al, 1992;de Paiva et al, 1999;Henkel et al, 1996;Lin et al, 2005;Ribchester et al, 1994;Smith and Betz, 1996). FM1-43 was applied for 5 minutes in the absence of stimulation before washing the preparation with cold Ca 2+ -free medium.…”
Section: Glycerotoxin Promotes the Long-term Upregulation Of Endocytosismentioning
confidence: 99%